Lessons and Legacies XII : New Directions in Holocaust Research and Education - Cole, Tim, 1970-; Gigliotti, Simone; Faulkner Rossi, Lauren; Lower, Wendy; Horowitz, Sara R., 1951-; Smelser, Ronald M., 1942-; Herzog, Dagmar, 1961-; Diefendorf, Jeffry M., 1945-; Hayes, Peter, 1946 September 7- (Book collections on Project MUSE., 1991)
"In the courtroom and the classroom, in popular media, public policy, and scholarly pursuits, the Holocaust-its origins, its nature, and its implications-remains very much a matter of interest, debate, and controversy. Arriving at a time when a new generation must come to terms with the legacy of the Holocaust or forever lose the benefit of its historical, social, and moral lessons, this volume offers a richly varied, deeply informed perspective on the practice, interpretation, and direction of Holocaust research now and in the future. In their essays the authors-an international group including eminent senior scholars as well those who represent the future of the field-set the agenda for Holocaust studies in the coming years, even as they give readers the means for understanding today's news and views of the Holocaust, whether in court cases involving victims and perpetrators; international, national, and corporate developments; or fictional, documentary, and historical accounts. Several of the essays-such as one on nonarmed "amidah" or resistance and others on the role of gender in the behavior of perpetrators and victims-provide innovative and potentially significant interpretive frameworks for the field of Holocaust studies. Others; for instance, the rounding up of Jews in Italy, Nazi food policy in Eastern Europe, and Nazi anti-Jewish scholarship, emphasize the importance of new sources for reconstructing the historical record. Still others, including essays on the 1964 Frankfurt trial of Auschwitz guards and on the response of the Catholic Church to the question of German guilt, bring a new depth and sophistication to highly charged, sharply politicized topics. Together these essays will inform the future of the Holocaust in scholarly research and in popular understanding."--Publisher's description.